Collected Papers, Volume 1 : Mind and Language, 1972-2010. - Stich, Stephen (Oxford University Press, USA, 2011)
This volume collects the best and most influential essays that Stephen Stich has published in the last 40 years on topics in the philosophy of mind and the philosophy of language. They discuss a wide range of topics including grammar, innateness, reference, folk psychology, eliminativism, connectionism, evolutionary psychology, simulation theory, social construction, and psychopathology. However, they are unified by two central concerns. The first is the viability of the commonsense conception of the mind in the face of challenges posed by both philosophical arguments and empirical findings. T.